Identification of a physiological role for leptin in the regulation of ambulatory activity and wheel running in mice - Morton, Gregory J.; Kaiyala, Karl J.; Fisher, Jonathan D.; Ogimoto, Kayoko; Schwartz, Michael W.; Wisse, Brent E. (American journal of physiology: endocrinology and metabolism, 2011)
Mechanisms regulating spontaneous physical activity remain poorly characterized despite evidence of influential genetic and acquired factors. We evaluated ambulatory activity and wheel running in leptin-deficient ob/ob mice and in wild-type mice rendered hypoleptinemic by fasting in both the presence and absence of subcutaneous leptin administration. In ob/ob mice, leptin treatment to plasma levels characteristic of wild-type mice acutely increased both ambulatory activity (by 4,000 ± 200 beam breaks/dark cycle, P < 0.05) and total energy expenditure (TEE; by 0.11 ± 0.01 kcal/h during the dark cycle, P < 0.05) in a dose-dependent manner and acutely increased wheel running (+350%, P < 0.05). Fasting potently increased ambulatory activity and wheel running in wild-type mice (AA: +25%, P < 0.05; wheel running: +80%, P < 0.05), and the effect of fasting was more pronounced in ob/ob mice (AA: +400%, P < 0.05; wheel running: +1,600%, P < 0.05). However, unlike what occurred in ad libitum-fed ob/ob mice, physiological leptin replacement attenuated or prevented fasting-induced increases of ambulatory activity and wheel running in both wild-type and ob/ob mice. Thus, plasma leptin is a physiological regulator of spontaneous physical activity, but the nature of leptin's effect on activity is dependent on food availability.